Growth Promotion and Secondary Metabolites of Vegetables by Spraying Soil with Psidium guajava, Aloe vera, Allium sativum and Medicago sativa Extracts at Various Stages of Growth - Ei Ei; Hyun Hwa Park; Yong In Kuk (Plants)
There is a growing need for sustainable, efficient methods to promote plant growth and protect crops, with plant extracts offering natural, multi-component solutions. Based on previous observations, Psidium guajava, Aloe vera, Allium sativum and Medicago sativa were selected from 17 water extracts to investigate how the application times of soil sprays affect the antioxidant enzymes and secondary metabolites in fruity and leafy vegetables at different growth stages. From 1 week after sowing (WAS) to 4 WAS, all applications increased the shoot fresh weight by 42–69% in cucumbers, 40–64% in tomatoes, 46–65% in kale and 42–63% in lettuce. These applications also increased the photosynthesis, flavonoids and antioxidative enzymes (ascorbate peroxide (APOD) and guaiacol peroxidase (GPOD)), which provided the plants with a balanced supply of nutrients essential for growth. In the real world, these results show that the use of natural extracts (P. guajava and A. sativum) can be a sustainable, eco-friendly alternative to synthetic fertilizers and pesticides, helping to improve crop yields and metabolism without harming the environment. This approach could reduce the reliance on chemical inputs and promote more sustainable agricultural practices, especially in controlled environments, like greenhouses, where crops like cucumbers and kale are grown.